(untitled) (Journal of Parents and Teachers, 2014)
This last presentation of the miniseries “The teacher’s portfolio” tries to guide. The portfolio is a tool of professional training to guide and orientate the teacher in their personal objectives to collect resources, to share findings with colleagues and supervisors and to gather stages. It must include a series of essential elements: an index, a self portrait, personal philosophy of education, establishment of real aims oriented to a real practice in the class and the identification of human and material resources that allows oneself development.